ТЕХНІЧНА РЕАЛІЗАЦІЯ ТА ДОСЛІДЖЕННЯ ЕКСПЕРИМЕНТАЛЬНОГО ЗРАЗКА ВЕНТИЛЬНО-ІНДУКТОРНОГО СТАРТЕР-ГЕНЕРАТОРА - Мазуренко, Л.І.; Джура, О.В.; Шихненко, М.О.; Білик, О.А. (Інститут електродинаміки Національної академії наук України, 2020)
The switched reluctance machine is considered as an alternative to starter-generators based on asynchronous and DC machines. An experimental sample structural diagram of the switched reluctance starter-generator is presented. Experimental research of the starter-generator in the motor mode when starting with the presence of the phase current level regulation were carried out. The operation of the switched reluctance starter-generator in the generator mode was investigated, quasi-steady-state and transient processes caused by a change in load were analyzed. Herewith dynamic and static quality indicators were determined during throw and drop the load: transient processes duration, DC voltage transient and steady deviation, its ripple coefficient and harmonic composition were established. It is shown that the generated electrical energy in quality meets the relevant standards. Data from experimental research confirm the possibility of using the switched reluctance machine as a starter generator when executed in accordance with the technical solution described in the article. References 10, figures 5, table.